Influence of ethosuximide on metrazol-induced seizures during ontogenesis in rats - Mares, P; Velísek, L (Activitas nervosa superior, 1983)
Effects of metrazol (pentylenetetrazole and ethosuximide were studied in male albino rats aged 7, 12, 18 and 90 days. The 18-day-old rats exhibited the highest sensitivity to metrazol. CD50s in the remaining three age groups were nearly the same. Ethosuximide was reliably effective against metrazol only in adult rats; in young animals it did not significantly change CD50s. Metrazol induced in ethosuximide-pretreated young rats either modified (long-lasting minimal seizures in 18-day-old animals) or new seizure patterns (minimal seizures in 7- and 12-day-old rats).
Keywords: Aging; krysa rodu Rattus; Animals; Pentylenetetrazole; vztah mezi dávkou a účinkem léčiva; Ethosuximide; pentylentetrazol; mužské pohlaví; zvířata; Dose-Response Relationship, Drug; Male; Seizures; ethosuximid; inbrední kmeny potkanů; Rats; stárnutí; záchvaty; Rats, Inbred Strains